Upward-scaling tipping cascades to meet climate goals: plausible grounds for hope. (21st April 2021) - Sharpe, Simon; Lenton, Timothy M.
ABSTRACT: Limiting global warming to well below 2°C requires a dramatic acceleration of decarbonization to reduce net anthropogenic greenhouse gas emissions to zero around mid-century. In complex systems – including human societies – tipping points can occur, in which a small perturbation transforms a system. Crucially, activating one tipping point can increase the likelihood of triggering another at a larger scale, and so on. Here, we show how such upward-scaling tipping cascades could accelerate progress in tackling climate change. We focus on two sectors – light road transport and power – where tipping points have already been triggered by policy interventions at individual nation scales. We show how positive-sum cooperation, between small coalitions of jurisdictions and their policymakers, could lead to global changes in the economy and emissions. The aim of activating tipping points and tipping cascades is a particular application of systems thinking. It represents a different starting point for policy to the theory of welfare economics, one that can be useful when the priority is to achieve dynamic rather than allocative efficiency. Key policy insights Pricing policies and targeted investments that bring clean technologies below the threshold of cost-parity with fossil fuel technologies can trigger reinforcing feedbacks that cascade up scales to propel disproportionately rapid decarbonization. Traditional approaches to climate policy based on welfare economics principles of minimizing marginal abatement costs, and pricing externalities, are likely to miss these opportunities. Systems thinking can help identify ways for policy to drive effective change. Positive-sum cooperation between small groups of countries can accelerate the activation of tipping points in the global economy, facilitating decarbonization in all countries. Early opportunities for this are in the power and light road transport sectors, where clean technologies are increasingly competitive with fossil fuels. The value of decarbonization policies should be judged not just on their immediate effects on emissions within the implementing jurisdiction, but also for their potential to contribute to upward-scaling tipping cascades in the global economy.